Uzbekistan: New Milestones of Higher Education Internationalization - E. F. Troitskiy; S. M. Yun (Высшее образование в России, 2021)
Modern Uzbekistan undergoes wide-scale social and economic reforms that include the modernization of higher education system. This paper aims at evaluating the actual and potential impact of the reforms in Uzbekistan’s higher education on the Russian universities’ opportunities to export education to Uzbekistan. Accordingly, the paper traces the evolution of the national higher education system under President Islam A. Karimov (from 1991 to 2016), analyzes the new priorities of higher education policies set by his successor Shavkat M. Mirziyoyev, shows their interlinkages with the transition to a new model of national development, and focuses on the objectives and instruments of higher education internationalization. Theoretically and methodologically, the research relies on the concepts of internal and external internationalization of higher education, Clark’s model of higher education system elements, and Trow’s concept of higher education massification levels. The authors show the scale and interconnectedness of higher education challenges that have been developing in Uzbekistan in the course of the 25 years of its independence. The authors argue that higher education internationalization has become a way to achieve a number of objectives, in particular to improve the quality of higher education, orient it to massification, make it more accessible in the country’s regional centers. The paper shows the parameters of internal and external internationalization of higher education in Uzbekistan that has demonstrated the unprecedented dynamics in post-Soviet countries. The paper underlines that the policy of rapprochement with Russia launched by Tashkent in 2016 has created exceptionally beneficial opportunities for Russian universities to work in Uzbekistan and attract Uzbek students. Four mid-term scenarios of higher education internationalization in Uzbekistan are suggested.